A Critical Study of the Cultural Impact of Western Imperialism among the Hausa Muslim Women of Northern Nigeria - Bunza, Mukhtar Umar; Kware, Aliyu Abubakar (2015)
European colonization, and subsequent occupation and imperialism in most parts of Africa and Asia, since the late 19th century, have been associated with a number radical changes and transformation in almost all façades of life of the natives. There were changes in governance, economy, socio-cultural norms and even worldview. One of the conspicuous aspects where the impacts of British imperialism could be seen in the Muslim dominated areas of northern Nigeria, as in other Muslim communities in the world, is in the conduct and outlook of the women folk. The study, thus, examines the transitions and switches undergone by women from the nineteenth century reform led by a revivalist scholar Shehu Usmanu Danfodiyo, d. 1817, that changed the temperament of women from what was then perceived as the exploitative condition instituted by the Hausa state system and culture contrary to Islamic stand on women liberty and freedom especially to education and other rights, which the new movement represented. In the same vein, in the beginning of the twentieth century, British occupied the areas and territories hitherto controlled by the Sokoto Caliphate founded as a result of the reform movement that started in 1804. The British replaced or transformed the existing rules and institutions founded by Danfodiyo, with what they considered as internationally accepted norms of English ethics. It is the impacts of the new systems introduced by the British on the societal structure as it affected and influenced the behaviour and social ethos of the women folk in particular that this research investigates.
Keywords: Hausa Muslim Women; Northern Nigeria; Western Cultural Imperialism